How does practice matches land laws in Central Asia? - Zarema Akhmadiyeva; Thomas Herzfeld (Land Use Policy, 2021)
This paper aims to explore the association between discrepancies in land rights and actual practices on the one hand and farmers' intentions to increase agricultural production on the other hand. We use farm-level data collected during a survey conducted in 2019 in southern Kazakhstan and eastern Uzbekistan and compare perceptions with land legislations of both countries. Comparative analysis of tenure conditions revealed that Kazakh farmers are less restricted in land use than Uzbek farmers. Moreover, insufficient law enforcement allows Kazakh farmers to violate existing restrictions on land transferability. Uzbek farmers tend to underuse their rights in such crucial issues as income generating and withdrawal of products from the land; the reason lies in inconsistency between land code and supplementary decrees for strategic crops. Our empirical findings show that mismatches between land rights on paper and perceived land rights -~that might be the violation of law restrictions or incomplete use of land rights -~generally reduces farmers' willingness to increase production.
Keywords: 630; land rights; land intensification; tenure security